Methodological challenges in the measurement of police cynicism : a critique of the Niederhoffer's police cynicism scale as applied in the South African Police Service (SAPS) - Mokotedi, Prince Nkitsing (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2010.